Modernity in Islamic tradition : the concept of 'society' in the journal al-Manar (Cairo, 1898-1940) - Zemmin, Florian, 1981- (Religion and society (Hague, Netherlands) ;, 2018)
What does it mean to be modern? This study regards the concept of 'society' as foundational to modern self-understanding. Identifying Arabic conceptualizations of society in the journal al-Manar, the mouthpiece of Islamic reformism, the author shows how modernity was articulated from within an Islamic discursive tradition. The fact that the classical term umma was a principal term used to conceptualize modern society suggests the convergence of discursive traditions in modernity, rather than a mere diffusion of European concepts.